Analysis of Acehnese Entries in the Great Dictionary of Indonesian Language: a Lexicographic Review - Nuthihar, Rahmad; Syihabuddin, NFN; Sunendar, Dadang; Matondang, Zulfamirda; Zainun, NFN; Rizki, Azrul (Balai Bahasa Kalimantan Tengah, 2024)
This article discusses Acehnese entries found in the Great Dictionary of the Indonesian Language (KBBI). The objective of this study is to assess the contribution of the Acehnese language in the KBBI based on lexicographic aspects. This study employs a qualitative descriptive research design with lexicographic approach. All data were collected on April 20, 2024, using document analysis techniques. The results of this study conclude that there are 142 entries in the KBBI originating from the Acehnese language. Of these 142 entries, 97 or 68.31% are nouns, 32 or 22.54% are verbs, 1 or 0.70% is adverb, 8 or 5.63% are adjectives, 1 or 0.70% are phrases, and 3 or 2.11% are not classified. Acehnese entries contribute only 0.12% of the 120,551 entries in the KBBI. Acehnese entries in the KBBI consist of basic word entries, compound words, and phrases. Reviewed by form, Acehnese basic entries consist of words and compound words. In terms of meaning, there are 26 Acehnese entries with homonym numbers and 2 entries that are polysemous. This study also found the writing of combinations of vowels and consonants different from the Standard Spelling Guidelines (EYD). Acehnese entries in the KBBI include vowel combinations such as ue, ie, and ui, while consonant combinations include ph, bl, dr, kr, pl. It is hoped that the latest edition of the Standard Spelling Guidelines (EYD) will accommodate vowel and consonant combinations from the Acehnese language.